Preparation method and new application of FeOOH / carbon aerogel material suitable for large-scale production
FeOOH@carbon aerogel material is prepared by combining the reaction of iron salt and copper salt on the basis of carbon aerogel and sodium hydroxide, which solves the problem of long preparation process of existing FeOOH material and the need to add surfactant. problem, achieving efficient and stable large-scale production, and significantly improving the adsorption performance of Mn(II) in water.
Patent Information
- Application Number
- CN202411680338.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-01-17
AI Technical Summary
The existing hydrolysis and precipitation methods have problems such as the preparation process taking a long time, the need to add surfactants, and the difficulty in large-scale production.
Carbon aerogel is reacted with sodium hydroxide under a certain mass ratio and heating conditions to generate alkali-modified carbon aerogel, and then reacted with iron salt and copper salt under another certain mass ratio and heating conditions to prepare FeOOH@ Carbon airgel material.
The rapid and stable synthesis of FeOOH@carbon airgel materials is achieved without the need to add surfactants. The production efficiency is increased by more than 50%. The product quality is stable, suitable for large-scale production, and shows excellent Mn(II) adsorption performance in water.
Smart Images

Figure CN119318942A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of carbon aerogel materials, and in particular relates to a preparation method, product and application of a FeOOH@carbon aerogel material. Background Art
[0002] Mining production is prone to environmental pollution, among which metal ion pollution is a prominent problem. Excessive metal ions have a profound impact on human health and environmental ecology. Among them, the outer electron configuration of manganese is 3d 5 4s 0 The d orbital is half-filled and has high stability. The removal of manganese in polymetallic polluted water is difficult and needs to be solved urgently.
[0003] Carbon aerogel, as a carbon nanomaterial with a three-dimensional porous network structure, has attracted widespread attention due to its high specific surface area, high porosity, mesoporous structure and other advantages. It has been studied and applied in supercapacitors, ion exchange resins, gas diffusion, hydrogen storage, lithium-ion battery negative electrodes and adsorption. Carbon aerogel is usually prepared by gelation, drying and carbonization of phenol (phenol, resorcinol, etc.) and aldehyde (formaldehyde, furfural, etc.) monomers in solution. In order to further improve the structural morphology of carbon aerogel, enhance its performance and expand its application range, it is often subjected to surface modification and structural modification. Common modification methods of carbon aerogel include metal doping, non-metal doping, surface modification, activation, etc.
[0004] Iron oxyhydroxide (FeOOH) is widely present in the natural environment. Due to its high specific surface area and stable physical and chemical properties, it is widely used in adsorption, catalysis, and pigment production. The surface of FeOOH contains a large number of hydroxyl (-OH) groups, which is conducive to chemical modification and has strong adsorption capacity. It is widely used in the removal of metal ions in water and the degradation of organic matter. The commonly used methods for preparing FeOOH are hydrolysis and precipitation. Surfactants are usually added to control the synthesis of FeOOH. The aging time required for synthesis ranges from 3 days to more than 7 days, which is not conducive to commercial promotion and application.
[0005] Therefore, it is of practical significance to develop a method for quickly and stably synthesizing FeOOH@carbon aerogel without the addition of surfactants and apply it to the removal of manganese in water.
[0006] Chinese patent CN202111012200.5 discloses a method for synthesizing nano-ribbon or rod-shaped FeOOH, which is prepared by dissolving trivalent iron salt in deionized water, adding urea, stirring and dissolving, and then adding sodium dodecyl sulfonate, stirring and dissolving, and transferring to a hydrothermal kettle for reaction, and finally preparing nano-ribbon FeOOH, wherein changing the type of surfactant (polyacrylic acid, polyvinyl pyrrolidone and sodium dodecylbenzene sulfonate) can obtain nano-rod-shaped FeOOH. However, this synthesis method requires the use of multiple surfactants, which is not only costly, but also difficult to be applied on a large scale in industry. Summary of the invention
[0007] The purpose of the present invention is to provide a method for preparing FeOOH@carbon aerogel material with short reaction time, stable and controllable product quality and suitable for large-scale production, in view of the technical difficulties existing in the existing hydrolysis method and precipitation method for synthesizing FeOOH materials, such as long preparation process, need to add surfactant, and difficulty in large-scale production.
[0008] Another object of the present invention is to provide a new application of the FeOOH@carbon aerogel material.
[0009] In order to achieve the above-mentioned object of the present invention, a preparation method of FeOOH@carbon aerogel material suitable for large-scale production of the present invention is implemented by the following technical scheme:
[0010] S1 carbon aerogel is dissolved in water, sodium hydroxide is dissolved in water, the two are respectively added into a reaction container and mixed and heated, after reaction, washed and dried to obtain alkali-modified carbon aerogel; the mass ratio of the carbon aerogel to sodium hydroxide is 1: (2.7-4.0); the heating temperature is controlled at 45-60°C, and the reaction time is controlled at 8-12h;
[0011] S2 iron salt is dissolved in water, copper salt is dissolved in water, and the alkali-modified carbon aerogel obtained in step S1 is dissolved in water; the three are respectively fed into a reaction container for mixing and heating, and after the reaction, FeOOH@carbon aerogel material is obtained by washing and drying; the mass ratio of iron salt, copper salt and alkali-modified carbon aerogel is (1.7-2.2): (0.3-1): 1, the heating temperature is controlled at 135-155°C, and the reaction time is controlled at 20-26h.
[0012] Preferably, the iron salt is ferric chloride hexahydrate; and the copper salt is copper sulfate pentahydrate.
[0013] In step S1, the mass ratio of the carbon aerogel to sodium hydroxide is 1:(2.7-3.3), the heating temperature is controlled at 47-55°C, and the reaction time is controlled at 9-11h, with the heating temperature of 50°C and the reaction time of 10h being optimal;
[0014] In step S2, the heating temperature is controlled at 140-150°C, and the reaction time is controlled at 23-25h, with the heating temperature of 150°C and the reaction time of 24h being optimal.
[0015] Preferably, the mass ratio of iron salt, copper salt and alkali-modified carbon aerogel is (1.9-2.1):(0.8-1):1.
[0016] Preferably, in step S1, the mass ratio of carbon aerogel to sodium hydroxide is 1:3; in step S2, the mass ratio of the iron salt, copper salt and alkali-modified carbon aerogel is 2:1:1.
[0017] The carbon aerogel used in step S1 of the present invention is a commercially available product purchased from China Steel Ma'anshan Mining Institute New Materials Technology Co., Ltd. (hereinafter referred to as China Steel Mining Institute New Materials Company).
[0018] The invention discloses a new application of FeOOH@carbon aerogel material suitable for large-scale production. The FeOOH@carbon aerogel material is used for treating wastewater containing Mn(II). The FeOOH@carbon aerogel material is added to the wastewater containing Mn(II) as an adsorbent to adjust the pH value of the wastewater containing Mn(II) to 6.0-7.0. The amount of the FeOOH@carbon aerogel material added is: 800-1200 grams of the FeOOH@carbon aerogel material is added to each cubic meter of the Mn(II) wastewater.
[0019] Furthermore, the Mn(II) concentration in the Mn(II)-containing wastewater is 0.1-20 mg / L.
[0020] Furthermore, the FeOOH@carbon aerogel material is added to the wastewater containing Mn(II), stirred and mixed to react for 6-9 hours, and then the FeOOH@carbon aerogel material loaded with Mn(II) is filtered out.
[0021] The preparation method and new application of FeOOH@carbon aerogel material suitable for large-scale production of the present invention adopt the above technical scheme, which has the following beneficial effects:
[0022] (1) Compared with the commonly used hydrolysis method and precipitation method, the preparation method of the present invention does not require the addition of surfactants or long-term aging, and the production efficiency is increased by more than 50%. In addition, the reaction process is reliable and the product quality is stable.
[0023] (2) The preparation method of the present invention can stably synthesize and prepare FeOOH@carbon aerogel materials within a certain reaction temperature range and material ratio range, and is suitable for large-scale production.
[0024] (3) The FeOOH@carbon aerogel prepared by the method of the present invention has C, Fe, and O elements, has abundant oxygen-containing functional groups, provides active sites, has excellent adsorption performance for Mn(II) in water, and can be used to remove Mn(II).
[0025] (4) Compared with traditional adsorbents, the FeOOH@carbon aerogel material prepared by the method of the present invention can achieve a removal rate of nearly 100% for 10 mg / L Mn(II) in water and a removal rate of up to 91.2% for 20 mg / L Mn(II), which is extremely effective. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The XRD diagrams of the FeOOH@carbon aerogel material obtained in Example 1 of the method of the present invention, the carbon aerogel used as raw materials, and FeOOH.
[0027] Figure 2 This is the XRD diagram of the FeOOH@carbon aerogel material obtained in Comparative Example 1.
[0028] Figure 3 This is a SEM image of the FeOOH@carbon aerogel material obtained in Example 1 of the method of the present invention. DETAILED DESCRIPTION
[0029] To better describe the present invention, the preparation method and new application of FeOOH@carbon aerogel material suitable for large-scale production of the present invention are further described in detail below in conjunction with the accompanying drawings and examples. If no specific conditions are specified in the examples, they are carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially. The scope of protection of the present invention is not limited by the following examples.
[0030] Example 1
[0031] Example Preparation of FeOOH@carbon aerogel material includes the following steps:
[0032] (1) Weigh 1.0 g of carbon aerogel material (purchased from China Iron and Steel Mining Research Institute New Materials Company) and dissolve it in 25 mL of water.
[0033] (2) Weigh 3.0 g of sodium hydroxide and dissolve it in 25 mL of water.
[0034] (3) The solutions in (1) and (2) were mixed so that the mass ratio of carbon aerogel to sodium hydroxide was close to 1:3, and the mixture was transferred into a glass conical flask.
[0035] (4) Set the operating parameters of the heating reflux device to 50°C and 10h, and start the operation.
[0036] (5) After the synthesis is completed, the sample is removed and centrifuged. The separated solid is washed three times with water and ethanol, centrifuged three times, and dried in a vacuum drying oven at 70° C. to obtain an alkali-modified carbon aerogel material.
[0037] (6) Weigh 1.0 g of ferric chloride hexahydrate and dissolve it in 5 mL of water.
[0038] (7) Weigh 0.5 g of copper sulfate pentahydrate and dissolve it in 5 mL of water.
[0039] (8) Weigh 0.5 g of the alkali-modified carbon aerogel material obtained in steps (1) to (5) and dissolve it in 15 mL of water.
[0040] (9) The solutions in (6), (7) and (8) are mixed, and the mass ratio of ferric chloride hexahydrate, copper sulfate pentahydrate and alkali-modified carbon aerogel material is close to 2:1:1, and then transferred into a reaction kettle.
[0041] (10) Set the operating parameters of the blast drying oven to 150°C and a reaction time of 24 h.
[0042] (11) Place the reactor in a forced air drying oven and start operation.
[0043] (12) After the synthesis is completed, the sample is removed and centrifuged. The separated solid is washed three times with water and ethanol and centrifuged three times. The synthesized FeOOH@carbon aerogel is dried in a vacuum drying oven at 70° C. to obtain a FeOOH@carbon aerogel material.
[0044] Example 2
[0045] This embodiment adopts a method for synthesizing FeOOH@carbon aerogel, which includes the following steps:
[0046] (1) Weigh 3.0 g of carbon aerogel material (purchased from China Iron and Steel Mining Research Institute New Materials Company) and dissolve it in 75 mL of water.
[0047] (2) Weigh 9.0 g of sodium hydroxide and dissolve it in 75 mL of water.
[0048] (3) The solutions in (1) and (2) were mixed so that the mass ratio of carbon aerogel to sodium hydroxide was close to 1:3, and the mixture was transferred into a glass conical flask.
[0049] (4) Set the operating parameters of the heating reflux device to 50°C and 10h, and start the operation.
[0050] (5) After the synthesis is completed, the sample is removed and centrifuged. The separated solid is washed three times with water and ethanol, centrifuged three times, and dried in a drying oven at 70° C. to obtain an alkali-modified carbon aerogel material.
[0051] (6) Weigh 2.0 g of ferric chloride hexahydrate and dissolve it in 10 mL of water.
[0052] (7) Weigh 0.9 g of copper sulfate pentahydrate and dissolve it in 10 mL of water.
[0053] (8) Weigh 1.0 g of the alkali-modified carbon aerogel material obtained in steps (1) to (5) and dissolve it in 25 mL of water.
[0054] (9) The solutions in (6), (7) and (8) are mixed, and the mass ratio of ferric chloride hexahydrate, copper sulfate pentahydrate and alkali-modified carbon aerogel material is close to 2:1:1, and then transferred into a reaction kettle.
[0055] (10) Set the operating parameters of the blast drying oven to 150°C and a reaction time of 24 h.
[0056] (11) Place the reactor in a forced air drying oven and start operation.
[0057] (12) After the synthesis is completed, the sample is removed and centrifuged. The separated solid is washed three times with water and ethanol and centrifuged three times. The synthesized FeOOH@carbon aerogel is dried in a drying oven at 70°C to obtain FeOOH@carbon aerogel material.
[0058] Application Example 1
[0059] 0.01 g of FeOOH@carbon aerogel was weighed and added to a pH = 6.0 aqueous solution containing 10 mg / LMn(II), and ultrasonic-assisted mixing was performed. The reaction was allowed to stand for 7 h, and the loaded FeOOH@carbon aerogel was filtered out. The adsorption rate (E%) was calculated (experimental data are shown in Table 1).
[0060] Application Example 2
[0061] 0.01 g of FeOOH@carbon aerogel was weighed and added to an aqueous solution containing 20 mg / LMn(II) at pH = 7.0, and ultrasonic-assisted mixing was performed. The mixture was allowed to react for 7 h, and the loaded FeOOH@carbon aerogel was filtered out. The adsorption rate (E%) was calculated (experimental data are shown in Table 1).
[0062] Table 1 shows the test results of using the FeOOH@carbon aerogel material prepared by the method example of the present invention as an adsorbent to remove Mn(II) from water.
[0063] Table 1 FeOOH@carbon aerogel as adsorbent for removal of Mn(II) from water
[0064]
[0065]
[0066] Note: C0 is the initial concentration of the ion in the solution; Ce is the concentration of the ion in the solution after the reaction.
[0067] Comparative Example
[0068] This comparative example adopts a method for synthesizing FeOOH@carbon aerogel, which comprises the following steps:
[0069] (1) Weigh 1.0 g of carbon aerogel material (purchased from China Iron and Steel Mining Research Institute New Materials Company) and dissolve it in 25 mL of water.
[0070] (2) Weigh 3.0 g of sodium hydroxide and dissolve it in 25 mL of water.
[0071] (3) The solutions in (1) and (2) were mixed so that the mass ratio of carbon aerogel to sodium hydroxide was close to 1:3, and the mixture was transferred into a glass conical flask.
[0072] (4) Set the operating parameters of the heating reflux device to 50°C and 10h, and start the operation.
[0073] (5) After the synthesis is completed, the sample is removed and centrifuged. The separated solid is washed three times with water and ethanol, centrifuged three times, and dried in a drying oven at 70° C. to obtain an alkali-modified carbon aerogel material.
[0074] (6) Weigh 1.0 g of ferric chloride hexahydrate and dissolve it in 10 mL of water.
[0075] (7) Weigh 0.5 g of the alkali-modified carbon aerogel material obtained in steps (1) to (5) and dissolve it in 15 mL of water.
[0076] (8) The solutions in (6) and (7) are mixed, and the mass ratio of ferric chloride hexahydrate and alkali-modified carbon aerogel material is close to 2:1, and then transferred into a reactor.
[0077] (9) Set the operating parameters of the blast drying oven to 150°C and a reaction time of 24 h.
[0078] (10) Place the reactor in a forced air drying oven and start operation.
[0079] (11) After the synthesis is completed, the sample is removed and centrifuged. The separated solid is washed three times with water and centrifuged three times. The synthesized FeOOH@carbon aerogel is dried in a drying oven at 70° C. to obtain FeOOH@carbon aerogel material.
[0080] Depend on Figure 1 From the XRD diagram of the FeOOH@carbon aerogel material obtained in Example 1 of the method of the present invention, it can be seen that the method of the present invention successfully loads FeOOH on the carbon aerogel material to obtain FeOOH@carbon aerogel, in which the FeOOH crystals can be attributed to β-FeOOH and have good crystallinity.
[0081] Depend on Figure 2 It can be seen from the XRD pattern of the FeOOH@carbon aerogel material obtained in Comparative Example 1 that in the comparative example, the XRD spectrum shows obvious diffraction peaks at around 2θ=33.1°, 40.8° and 54.1°.
[0082] The XRD pattern of the FeOOH@carbon aerogel material obtained in Example 2 of the method of the present invention is similar to that in Example 1.
[0083] Combination Figure 1 and Figure 3 It can be seen that the preparation method of the present invention obtains FeOOH@carbon aerogel with needle-like β-FeOOH morphology. β-FeOOH mineral itself is very easy to agglomerate into spheres or blocks, while the FeOOH loaded on the carbon aerogel of the present invention is evenly distributed without agglomeration, and the FeOOH needle-like particles are about 1-2μm in length.
[0084] The above is only a preferred specific implementation of the present invention, but it is obvious that the described embodiments are only a part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without creative work inspired by them, and any technicians familiar with the technical field within the technical scope disclosed by the present invention, according to the technical solution and inventive concept of the present invention, are equivalently replaced or changed, and should be covered within the protection scope of the present invention.
Claims
1. A method for preparing FeOOH@carbon aerogel material suitable for large-scale production, characterized in that The following technical solutions are adopted: S1 carbon aerogel is dissolved in water, sodium hydroxide is dissolved in water, the two are respectively added into a reaction container and mixed and heated, after reaction, washed and dried to obtain alkali-modified carbon aerogel; the mass ratio of the carbon aerogel to sodium hydroxide is 1: (2.7-4.0); the heating temperature is controlled at 45-60°C, and the reaction time is controlled at 8-12h; S2 iron salt is dissolved in water, copper salt is dissolved in water, and the alkali-modified carbon aerogel obtained in step S1 is dissolved in water; the three are respectively fed into a reaction container for mixing and heating, and after the reaction, FeOOH@carbon aerogel material is obtained by washing and drying; the mass ratio of iron salt, copper salt and alkali-modified carbon aerogel is (1.7-2.2): (0.3-1): 1, the heating temperature is controlled at 135-155°C, and the reaction time is controlled at 20-26h.
2. The method for preparing FeOOH@carbon aerogel material suitable for large-scale production according to claim 1, characterized in that: The iron salt is ferric chloride hexahydrate.
3. The method for preparing FeOOH@carbon aerogel material suitable for large-scale production according to claim 1, characterized in that: The copper salt is copper sulfate pentahydrate.
4. The method for preparing FeOOH@carbon aerogel material suitable for large-scale production according to claim 1, characterized in that: In step S1, the mass ratio of the carbon aerogel to sodium hydroxide is 1:(2.7-3.3), the heating temperature is controlled at 47-55° C., and the reaction time is controlled at 9-11 h.
5. The method for preparing FeOOH@carbon aerogel material suitable for large-scale production according to claim 1, characterized in that: In step S2, the heating temperature is controlled at 140-150°C, and the reaction time is controlled at 23-25h.
6. A method for preparing FeOOH@carbon aerogel material suitable for large-scale production as claimed in claim 1, 2, 3, 4 or 5, characterized in that: The mass ratio of iron salt, copper salt and alkali-modified carbon aerogel is (1.9-2.1):(0.8-1):
1.
7. A method for preparing FeOOH@carbon aerogel material suitable for large-scale production as claimed in claim 6, characterized in that: In step S1, the mass ratio of carbon aerogel to sodium hydroxide is 1:3; in step S2, the mass ratio of the iron salt, copper salt and alkali-modified carbon aerogel is 2:1:
1.
8. A new application of FeOOH@carbon aerogel material suitable for large-scale production as claimed in claim 1, 2, 3, 4 or 5, characterized in that: The FeOOH@carbon aerogel material is used for treating wastewater containing Mn(II). The FeOOH@carbon aerogel material is added to the wastewater containing Mn(II) as an adsorbent to adjust the pH of the wastewater containing Mn(II) to 6.0-7.
0. The amount of FeOOH@carbon aerogel material added is: 800-1200 grams of FeOOH@carbon aerogel material is added to each cubic meter of Mn(II) wastewater.
9. A new application of FeOOH@carbon aerogel material suitable for large-scale production as claimed in claim 8, characterized in that: The Mn(II) concentration in the Mn(II)-containing wastewater is 0.1-20 mg / L.
10. A new application of FeOOH@carbon aerogel material suitable for large-scale production as claimed in claim 9, characterized in that: The FeOOH@carbon aerogel material was added into the wastewater containing Mn(II), stirred and mixed for 6-9 hours, and then the FeOOH@carbon aerogel material loaded with Mn(II) was filtered out.
Citation Information
Patent Citations
Nanometer belt-shaped or rod-shaped FeOOH as well as preparation method and application thereof
CN113716616A